Enhancing the experience of needs satisfaction through service engagement: A case of commercial fitness centers in Malaysia - Ong, Derek Lai Teik * (Taylor & Francis for Korean Scholars of Marketing and Yonsei University, 2015)
The commercial fitness industry is booming in Malaysia and the competition that has built up means it is becoming more difficult to entice new members to fitness establishments. This research investigates the needs of those who are engaging with the services of these commercial fitness operators and analyses how this engagement plays a role in determining overall satisfaction with service. The Scale of Service Quality for Recreational Sport (SSQRS) was used for data collection and reveals that members are drawn more to interaction, outcome, physical environment quality and the engagement they receive from a gym membership more than to the programs that are offered. This study’s findings contribute to the development of marketing strategies to support sustainable growth of the fitness industry.